2015
DOI: 10.1177/1557988315579196
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Hispanic Male Intimate Partner Violence Perpetration

Abstract: The literature review analyzed 24 studies that explored male intimate partner violence (IPV) perpetration risk factors among men, in particular Hispanics, using the socioecological model framework composed of four socioecological levels for violence prevention. Six databases were reviewed within the EBSCO search engine for articles published from 2000 to 2014. Articles reviewed were specific to risk factors for IPV perpetration among Hispanic men, focusing particularly on Mexican American men. Many key factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
40
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 120 publications
3
40
1
1
Order By: Relevance
“…Prevalence of RC in samples of Latina women is 14% to 17% . 16 In studies of Latino men, unique factors have been identified as associated with IPV perpetration, including patriarchal gender role attitudes . These factors may also impact RC among Latina women but have not been studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prevalence of RC in samples of Latina women is 14% to 17% . 16 In studies of Latino men, unique factors have been identified as associated with IPV perpetration, including patriarchal gender role attitudes . These factors may also impact RC among Latina women but have not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…13,15,16 In studies of Latino men, unique factors have been identified as associated with IPV perpetration, including patriarchal gender role attitudes. 26 These factors may also impact RC among Latina women but have not been studied. Some studies note that Latina women with immigration concerns may be less ✦ Partners may exert coercive reproductive control over women by sabotaging contraceptive methods; verbally pressuring them to get pregnant or to end a pregnancy; threatening violence if the woman does not get pregnant or end a pregnancy; or blocking access to contraceptive, abortion, or prenatal services.…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol abuse ( Kantor, 1997 ; Neff, Holamon, & Schluter, 1995 ; Perilla, Bakemon, & Norris, 1994 ; West, Kantor, & Jasinski, 1998 ) and cocaine ( Coker, Smith, McKeown, & King, 2000 ; Parrott, Drobes, Saladin, Coffey, & Dansky, 2003 ) were also correlated with IPV perpetration. However, factors unique to men of Mexican origin including: Machismo , acculturation, and acculturation/acculturative stress may exist among men of Mexican origin (MMO) and augment their risk for IPV perpetration ( Mancera, Dorgo, & Provencio-Vasquez, 2015 ). Machismo , a term coined by anthropologists, and promulgated by journalists, and scholars has negative connotations and implies that Mexican/Latino men engage in negative behaviors such as violence, adultery, and drunkenness ( Gutmann & Viveros, 2005 ).…”
mentioning
confidence: 99%
“…The determinants that increase IPV perpetration risk among the rapidly growing population of Hispanic men of Mexican descent needs to be better understood ( Mancera et al, 2015 ) as the incidence of IPV perpetration among Hispanic couples has increased (14%) in comparison to non-Hispanic White couples (6%) ( Cummings, Gonzalez-Guarda, & Sandoval, 2013 ). The Patient Protection Affordable Care Act (2010) was expanded to include interpersonal and domestic violence screenings and counseling.…”
mentioning
confidence: 99%
“…18 In addition, less acculturated, low income immigrant Latina women are at high risk of being victims of intimate partner violence (IPV), which, in turn is associated with post-traumatic stress disorder and major depression. 19,20 …”
mentioning
confidence: 99%